Vertical profiles of temperature, wind, and turbulent fluxes across a deciduous forest over a slope observed with a UAV - Wrenger, Burkhard; Cuxart, Joan (Frontiers in Earth Science, 2024)
The Steinkrug forest is a deciduous forest over a slope in the Solling natural area in Lower Saxony (Germany), with a typical forest height of 30 m. Fifteen vertical flights made by an unmanned multicopter system near sunset between summer 2019 and spring 2020 are inspected, from the surface to 100 m above ground level. These measurements provide information on the vertical structure of wind and temperature within and above the canopy, including the effects of shallow slope flows near the ground. Contrasting measurements downhill outside the forest were also made. The gathered data allow estimated profiles of the turbulent fluxes of sensible heat and momentum to be obtained, by computing averages and fluctuations for layers of 5m-depth, and also to produce a leaf area density profile, both in leafy and leafless conditions. The presence of a slope flow is inspected at both sites and the applicability of existing theories is explored. Keywords: Unmanned aerial system Forested slope Wind and temperature profiles Momentum and heat flux profiles Forest with and without leaves *for the friction velocity we get u 2 * (h) = -u ′ w ′ (h) at the top of the canopy and u 2 * (z) = u 2 * (h cr )e L(z) (8)